2021
DOI: 10.3389/fitd.2021.788590
|View full text |Cite
|
Sign up to set email alerts
|

The Pandemic Experience in Southeast Asia: Interface Between SARS-CoV-2, Malaria, and Dengue

Abstract: Southeast Asia (SEA) emerged relatively unscathed from the first year of the global SARS-CoV-2 pandemic, but as of July 2021 the region is experiencing a surge in case numbers primarily driven by Alpha (B.1.1.7) and subsequently the more transmissible Delta (B.1.617.2) variants. While initial disease burden was mitigated by swift government responses, favorable cultural and societal factors, the more recent rise in cases suggests an under-appreciation of prior prevalence and over-appreciation of possible cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 74 publications
(66 reference statements)
1
4
0
Order By: Relevance
“…During the course of 125 ns MD simulation, the Delta variant maintained a much stable binding in complex with the SAS hACE2 compared with that of reference hACE2. This outcome is also notably consistent with the devastating spread of the variant in South-East Asia, as a large population of around 49.7 million in India alone would represent the SAS hACE2 harbouring the P84T substitution [ 76 ].…”
Section: Discussionsupporting
confidence: 63%
“…During the course of 125 ns MD simulation, the Delta variant maintained a much stable binding in complex with the SAS hACE2 compared with that of reference hACE2. This outcome is also notably consistent with the devastating spread of the variant in South-East Asia, as a large population of around 49.7 million in India alone would represent the SAS hACE2 harbouring the P84T substitution [ 76 ].…”
Section: Discussionsupporting
confidence: 63%
“…Cross-reactivity of samples from dengue serology as well as malaria serology samples have previously been reported to present false positive results on SARS-CoV-2 assays [16] . Therefore, whilst only 1 out of the 5 Dengue samples tested demonstrated this weak cross-reactivity on AbC-19™, this should still be taken into consideration to prevent overestimating SARS-CoV-2 seroprevalence in regions where these infections are widespread.…”
Section: Discussionmentioning
confidence: 99%
“…Recent mNGS studies in Uganda [ 14 ], Kenya [ 15 ], and Cambodia [ 11 ] have revealed new insights into the local patterns of infectious etiologies of non-specific disease presentations including fever and pneumonia. As recently underscored by the SARS-CoV-2 pandemic, unbiased disease surveillance can also provide insight with regard to incidence of newly emerging infections, especially in geographies where implementation of widespread, disease-specific diagnostics is constrained by competing demands on resources [ 16 ]. In addition to identifying the microbial composition of a sample, a key strength of the mNGS approach is the possibility to generate partial or whole pathogen genomes for downstream epidemiologic and genomic investigations.…”
Section: Introductionmentioning
confidence: 99%